The Role of Precedent Phenomena in Media Materials - Gavkhar Tuklieva Nurislamovna (Scholars Digest Publishing, 2023)
The study of media materials has increasingly placed great importance on understanding the role of precedent phenomena. Such phenomena refer to the ways in which previous events, stories, or trends have influenced the creation and reception of new media content. This article explores the importance of precedent phenomena in shaping media materials, including its impact on content creation, audience perception, and cultural trends. Drawing on a range of empirical studies and theoretical perspectives, the paper highlights both the benefits and limitations of relying on precedent phenomena in media production. Ultimately, it argues that a deeper understanding of precedent phenomena is crucial to crafting engaging, relevant, and impactful media content that resonates with contemporary audiences.
Keywords: linguoculturology, precedent phenomena, special features, functions, English journalistic texts.